Monetary integration has made progress - Leonhard Gleske (Intereconomics, 1989)
The European Monetary System was ten years old on 13th March. The following three contributions assess the progress made so far and the outlook for the future.
Keywords: 330; EMS Ten Years on: Assessment and Outlook; European Monetary System